2000
DOI: 10.1007/s004420000385
|View full text |Cite
|
Sign up to set email alerts
|

Morphotype community structure of ectomycorrhizas on Douglas fir ( Pseudotsuga menziesii Mirb. Franco) seedlings grown under elevated atmospheric CO 2 and temperature

Abstract: Mycorrhizas alter the acquisition of carbon and nutrients, thereby affecting numerous plant and ecosystem processes. It is important, therefore, to determine how mycorrhizal populations will change under possible future climate conditions. Individual and interactive effects of elevated atmospheric CO concentration and atmospheric temperature were assessed in a 2×2 factorial design [ambient and elevated (200 ppm above ambient) CO concentrations, and ambient and elevated (4°C above ambient) temperatures]. In Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 42 publications
(40 reference statements)
3
48
2
Order By: Relevance
“…This finding is contrary to a previous study examining the effects of warming on ectomycorrhizal fungal communities of Douglas-fir seedlings. Rygiewicz et al (2000) found an increase in the number of different mycorrhizal fungi on seedlings grown in controlled environment chambers with elevated temperatures compared to those grown in chambers with ambient temperatures. Differences in results between our study could be due to the following: (1) differences in how the hosts react to warming; (2) the age of the plant, as seedlings were used for their study while we sampled mature shrubs and (3) greater availability of fungal inoculum, which may be more widely dispersed at lower latitudes, providing greater opportunity for migration of new genotypes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is contrary to a previous study examining the effects of warming on ectomycorrhizal fungal communities of Douglas-fir seedlings. Rygiewicz et al (2000) found an increase in the number of different mycorrhizal fungi on seedlings grown in controlled environment chambers with elevated temperatures compared to those grown in chambers with ambient temperatures. Differences in results between our study could be due to the following: (1) differences in how the hosts react to warming; (2) the age of the plant, as seedlings were used for their study while we sampled mature shrubs and (3) greater availability of fungal inoculum, which may be more widely dispersed at lower latitudes, providing greater opportunity for migration of new genotypes.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings suggest that the root-associated fungal community at these tundra sites were quite resilient to warming, as evidenced by the lack of change in genotype richness or evenness (Kårén and Nylund, 1997;Rygiewicz et al, 2000). Over longer time periods, it would be interesting to know if sites with higher richness, such as the LG and UG sites, are more resilient than the UD site.…”
Section: Effect Of Experimental Warming Ke Fujimura Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the ecosystem level context dependencies (Compant et al 2010), interacting environmental drivers may further modulate the fungal community responses (Hayden et al 2012). For example, Rygiewicz et al (2000) showed that soil fungal community responses to elevated temperature differed between [CO 2 ] treatments. Heterotrophic fungal communities and their responses to shifts in environmental conditions are particularly important, because they are essential in carbon and nutrient cycling (Dighton 2003), comprise a large recalcitrant belowground carbon sink (Treseder & Allen 2000), and may be affected directly by the shifts in the environmental drivers or indirectly through the responses in plant communities (Cregger et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these experiments have shown little effects of elevated CO2 in ectomycorrhizal community structure. Rygiewicz et al [27] planted two-year-old Pseudotsuga menziesii (Mirb.) Franco seedlings in chambers, and after four years of elevated CO2 exposure found small overall effects on the ectomycorrhizal morphotype community structure.…”
Section: Introductionmentioning
confidence: 99%